A Novel Method for Electricity Generation from Footsteps Using Piezoelectric Transducers (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The process of generation of mechanical energy of human footsteps and converting into electrical energy using piezoelectric transducer is discussed in this paper. This method of generation comes under the Energy scavenging section of renewable resources where wasted energy during regular processes such as heat during exothermic reactions is captured and converted. With the increase in energy consumption from handy electronic devices, the concept of harvesting alternative non-conventional energy in highly density population regions is a new interest of late. The model is a focused spring action between two tiles on to the piezoelectric transducers. This model contracts during a footstep and therefore allowing the mechanical input onto the transducers and converting this input into electrical output. This process is focused on footsteps upon multiple units across a pathway to generate maximum output with minimal monitoring. This type of generator is simply a secondary backup to coal or hydro power generation. The main feature of such generator is that this requires no conscious thought on the user’s part.